Early cognitive and quality of life changes after transfemoral transcatheter aortic valve replacement - Istrate, Mihnea; Dregoesc, Mihaela Ioana; Buiga, Victor Stefan; Redfern, Julien; Iancu, Adrian Corneliu (Medicine and Pharmacy Reports, 2025)
Background and aims. Cognitive impairment has been associated with the presence of severe aortic stenosis (AS). Our study evaluated the early changes in cognitive function and quality of life in patients with severe AS who underwent transfemoral transcatheter aortic valve replacement (TAVR). Methods. The cognitive function and quality of life of patients with severe symptomatic AS who underwent transfemoral TAVR were assessed with the Montreal Cognitive Assessment (MoCA) and the EQ-5D-3L questionnaire, respectively. The tests were performed at the time of admission and at 48 to 72 h after TAVR. Results. The study group included 37 patients with a mean age of 78 years. Cognitive improvement was observed in 72.9% of patients. A higher MoCA score at baseline was correlated with a better functional outcome after TAVR (r=0.49, p=0.02). Patients with an early post-procedural increase in MoCA scores had a smaller aortic valve area at baseline as compared to patients without cognitive improvement (0.5±0.2 vs. 0.7±0.1 sq.cm, p=0.02). The baseline aortic valve area was associated with an increase in MoCA scores at an optimal cutoff value ≤0.65 sq.cm (AUC 0.739; p=0.005). A significant increase in median EQ-5D-3L scores was observed between baseline and follow-up (60 (51-70) vs. 73 (65-80) points, p<0.001). The lack of improvement in functional status was associated with a prolonged stay in the Intensive Care Unit (ICU) (r=-0.46, p=0.02). Conclusions. In patients with severe symptomatic AS, a smaller aortic valve area at baseline was associated with an early cognitive improvement after transfemoral TAVR. Baseline cognition and the length of stay in the ICU influenced the early functional outcomes.